MODERN METHODS OF TREATING CEREBRAL PALSY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Treatment of cerebral palsy is a long and difficult process, and the participation of several specialists is considered necessary. In this case, it is considered advisable to involve a rehabilitation specialist, neurologist, art therapist, occupational therapist, kinesiologist, massage therapist, speech pathologist, pediatrician, deaf-mute therapist and a number of other specialists. Of course, parental involvement is considered very effective for homeschooling. Parental participation creates inner peace and confidence in the child and ensures long-term continuation of this rehabilitation. At this stage, we must not forget about drug treatment. If you put it all together, long-term, ongoing rehabilitation will certainly show its results